THE ROL OF TEMPERAMENT IN LANGUAGE ACQUISITION - Martínez Fuentes, María Teresa (Anales de Psicología / Annals of Psychology)
This study aimed to analyse the relationships between several temperamental dimensions and the early linguistic development. The temperament data were obtained by assessing laboratory structured tasks (Matheny & Wilson, 1981) presented to 12 infants when they were both 12 and 18 months old, and questionnaires (Goldsmith, 1987) filled out by parents when their infants were at ages of 15 and 18 months. The language measurements (vocabulary size and early linguistic style) were collected from the parents’ record of their infants’ language at ages of 15 and 18 months. Results suggest that some temperamental dimensions can be involved in the vocabulary size and the linguistic style in the first stages of language development.